HUMAN CAPITAL SEBAGAI PILAR ESENSIAL DALAM IMPLEMENTASI QUALITY MANAGEMENT SYSTEM (QMS) ISO 9001:2015 PADA INDUSTRI KIMIA SEBAGAI PENINGKAT DAYA SAING DILIHAT DARI PERSPEKTIF TEORITIS - Uli Wildan Nuryanto (Universitas Mercu Buana, 2018)
Currently, manufacturing industry in Indonesia hold the 40th position in the world. This condition is very unsatisfying. To improve performance of Indonesia's manufacturing industry specially the chemical industry, it needs to improve the performance by manage the standardized system. One way to ensure standardization of procedures is to make sure that all procedures done according to international industry requirements i.e. quality management system ISO 9001: 2015. The role of the ISO system is very important for companies to be able to increase credibility in the eyes of customers and stakeholders. Not only that, with the implementation of the quality management system ISO 9001: 2015, companies can increase employee productivity so that company performance can be achieved efficiently and effectively. Optimal performance is expected to improve the competitiveness and sustainability of the company. The process of implementing the quality management system ISO 9001: 2015 very well depends on carefully planned and measured human capital management. without systematic and structured planning of the human resources management, it will be very difficult for companies to obtain higher quality human resources which will results in potential obstacles in implementing the implementation of the quality management system ISO 9001: 2015. For this reason, it is obligatory for company to implement a business process approach in human capital management so as a quality-oriented organizational culture be achieved. in the end, this process can create organizational commitment in accordance with the basic principles of quality management system ISO 9001: 2015.